One-step floating conversion of biomass into highly graphitized and continuous carbon nanotube yarns - Gongxun Zhai; Qianqian Wang; Fuyao Liu; Zexu Hu; Chao Jia; Dengxin Li; Hengxue Xiang; Meifang Zhu (Green Energy & Environment, 2023)
The rapid growth of the demand for carbon nanotubes (CNTs) has greatly promoted their large-scale synthesis and development. However, the continuous production of CNT fibers by floating catalyst chemical vapor deposition (FCCVD) requires a large amount of non-renewable carbon sources. Here, the continuous production of highly graphitized CNT yarns from biomass tannic acid (TA) is reported. The chelation of TA and catalyst promotes the rapid cracking of biomass into carbon source gas, and the pyrolysis cracking produces the reducing gas, which solves the problems of the continuous production of CNT yarns using biomass. Through simple twisting, the mechanical strength of CNT yarn can reach 886 ± 46 MPa, and the electrical conductivity and graphitization (IG/ID) can reach 2 × 105 S m−1 and 6.3, respectively. This work presents a promising solution for the continuous preparation of CNT yarns based on green raw material.